Peranan Audit Kepatuhan Terhadap Instruksi Kerja di PT Bintan Bersatu Apparel - Pandiangan, Callen Back; Mukhlis, Mukhlis; Setiyanto, Adi Irawan; Priyartso, Sony (Journal of Applied Business Administration, 2024)
This research examines the role of compliance audits on work instructions at PT Bintan Bersatu Apparel, with a focus on employee understanding of compliance and factors influencing its effectiveness. The research method used a qualitative approach, involving informants such as internal staff auditors, Assistant Manager Pre- production, and department leaders. In this study, it was found that the level of employee compliance with work instructions at PT Bintan Bersatu Apparel varies and is influenced by several factors, including employee understanding, management support, and the clarity of Standard Operating Procedures (SOPs). The results of compliance audits play a crucial role in influencing the implementation of work instructions by identifying discrepancies and initiating necessary corrective actions. Factors such as knowledge, motivation, attitude, experience, internal auditor training, supervision, and the availability of clear SOPs also impact the effectiveness of compliance audits. Therefore, the recommendations put forth involve concrete steps, including improving employee understanding through structured training, active management support in monitoring and enforcing compliance, and refining SOPs to ensure clarity. Additionally, the importance of developing internal auditors, rigorous supervision, periodic evaluations of employee compliance, and providing constructive feedback are emphasized. By implementing these recommendations comprehensively, PT Bintan Bersatu Apparel can ensure optimal quality, productivity, and operational safety within their company.